Frontispiece: Tetrylones: An Intriguing Class of Monoatomic Zero‐valent Group 14 Compounds. Issue 38 (6th July 2018) - Majhi, Paresh Kumar; Sasamori, Takahiro
Abstract : Tetrylones represent a class of zero‐valent group 14 compounds with the general formula EL2 (E=C, Si, Ge, Sn, or Pb; L=neutral σ‐donating ligand). This Minireview focuses on the synthesis, structure, reactivity and computational examination of recently discovered heavier tetrylones (Si, Ge, Sn). See the article by P. K. Majhi and T. Sasamori onpage 9441 ff.